Self-Identity and Career Aspiration Among Millenial Student and Its Contribution on Career Guidance and Counseling Transformation - Muslihati,; Atmoko, Adi; Zen, Ella Faridati (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to describe the self-identity and career aspirations of millennial adolescents and its contribution to the conceptual design of transformative career counseling and guidance services in senior high school. This research idea is motivated by social change and the rapid development of information and communication technology within industry revolution 4.0. Social change in this era requires rapid response from education practitioners, especially academics of guidance and counseling. Career guidance and counseling is one of the important helping for youth to face career challenges of disruption era. This condition require the transformation in helping services. Qualitative with fenomenological design is utilized in this research. School counselor and senior high students in Malang was the key informans. The data was collected through focus group discussion. The results are student think that career guidance and counseling services need to be provided using information technology and social media. They also need update career information such as latest job description. Besides, school counselor realized that millenial generations has unique passion and career aspiration influenced by social media and rapid social and information technology change.This reseach imply on developing transformation in service management of school career guidance and counseling.